2015
DOI: 10.1590/s0100-720320150005367
|View full text |Cite
|
Sign up to set email alerts
|

Práticas alimentares de gestantes e mulheres não grávidas: há diferenças?

Abstract: ResumoOBJETIVOS: Conhecer o comportamento alimentar de gestantes assistidas pela atenção primária à saúde e compará-lo ao de mulheres em idade fértil das capitais brasileiras. MÉTODOS: Estudo transversal realizado no segundo trimestre gestacional com 256 gestantes, sorteadas dentre as assistidas pelas unidades de atenção primária à saúde de um município do interior paulista em 2009/2010. As práticas alimentares foram investigadas utilizando questionário adaptado do sistema Vigitel, composto por questões acerca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
2
7
0
8
Order By: Relevance
“…We also observed that few pregnant women reached the maximum score for the limit of consumption of ultra-processed foods, an unfavorable characteristic of the quality of the diet given the adverse effects of these foods on the health of individuals 21 , 23 . Similar to the data of this study, a high consumption of ultra-processed foods, such as soft drinks, crackers, and cookies, has also been found in a cross-sectional study carried out among pregnant women in the city of Botucatu, state of São Paulo, Brazil 9 .…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that few pregnant women reached the maximum score for the limit of consumption of ultra-processed foods, an unfavorable characteristic of the quality of the diet given the adverse effects of these foods on the health of individuals 21 , 23 . Similar to the data of this study, a high consumption of ultra-processed foods, such as soft drinks, crackers, and cookies, has also been found in a cross-sectional study carried out among pregnant women in the city of Botucatu, state of São Paulo, Brazil 9 .…”
Section: Discussionsupporting
confidence: 88%
“…During pregnancy, women adopt healthy eating habits to promote fetal development, as well as a better prognosis for childbirth and postpartum outcomes. However, some pregnant women exhibit unhealthy eating behaviors characterized by greater consumption of fast food , soft drinks, and other foods high in sugar and fat [1719].…”
Section: Introductionmentioning
confidence: 99%
“…Esses resultados corroboram aqueles reportados por Teixeira e Cabral (2016), que constataram hábitos alimentares adequados, diversificados e ricos em frutas e hortaliças entre gestantes adultas. Apesar disso, outros estudos têm indicado que as práticas alimentares de gestantes adultas também requerem melhorias, e que intervenções em educação alimentar e nutricional devem receber mais espaço na atenção prénatal, reforçando a importância dos hábitos alimentares na gestação, especialmente porque as gestantes serão responsáveis pela formação dos hábitos alimentares da criança que está sendo gerada (MELERE et al, 2013;GOMES et al, 2015).…”
Section: Discussionunclassified